2013
DOI: 10.3923/pjbs.2013.1223.1225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diuretic Activity of Different Extracts of Mimosa pudica Linn.

Abstract: In that study, Mimosa pudica linn was tested for diuretic activity using the lipschitz test. The ethanolic and aqoues extract of Mimosa pudica Linn. was studied at two dose level 100 and 200 mg kg(-1) b.wt. Furosemide (20 mg kg(-1) b.wt.) was used as standard drug in a 0.9% saline solution. Urine volumes were measured for all the groups up to 5 h. The ethanolic extract of Mimosa pudica linn was exhibited significant diuretic activity at doses of 100 and 200 mg kg(-1) b.wt. by increasing total urine volume and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Of these, M. pigra attenuated the development of experimental pulmonary hypertension, M. caesalpiniifolia Benth. induced vasorelaxant and hypotensive effects, and M. pudica , which showed diuretic and saluretic activities . Despite the biological potential evidenced by these studies, another species of interest, M. bimucronata (DC.)…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of these, M. pigra attenuated the development of experimental pulmonary hypertension, M. caesalpiniifolia Benth. induced vasorelaxant and hypotensive effects, and M. pudica , which showed diuretic and saluretic activities . Despite the biological potential evidenced by these studies, another species of interest, M. bimucronata (DC.)…”
Section: Introductionmentioning
confidence: 98%
“…induced vasorelaxant and hypotensive effects, [22] and M. pudica, which showed diuretic and saluretic activities. [23,24] Despite the biological potential evidenced by these studies, another species of interest, M. bimucronata (DC.) Kuntze, popularly known in Brazil as 'maric a' and of natural occurrence on the Brazilian coast, [25][26][27][28][29] has not yet been the subject of any scientific study regarding its possible phytochemical and pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…The Mimosa genus has also been the subject of studies to determine the possible diuretic effect of one of its species: M. pudica Linn, known as "dormideira" in Brazil and by numerous common names in English, including "sensitive plant", "humble plant", "shameplant", and "touch-me-not". Baghel et al [24] evaluated the diuretic effect of its aqueous and ethanolic extract in albino rats. The animals were orally treated with extract obtained from whole plant at doses of 100 and 200 mg/kg.…”
Section: Brazilian Medicinal Plants With Diuretic Potentialmentioning
confidence: 99%
“…were found a multitude of therapeutic properties. Diuretic [4], psoriasis cure [5], swelling, wounds healing [6], antioxidant, antimicrobial, antiinflammatory [7], antidiabetic, anticancer, cardiovascular disease [8], hypolipidemic, antimicrobial activity [9], anticonvulsant [10], antimalarial, antifertility, fistula [11], cough, influenza [12], systemic infections, snakebite areas [13], hepatoprotective activity [14], antidepressant [15], leprosy, hypoglycemic, pulmonary tuberculosis, neurasthenia [16], atherosclerosis, hyperglycemic [17], and various urogenital infections [18] have been attributed in different parts of M. pudica. Regarding the secondary metabolite potential of M. pudica, it has been reported that it contains nitrogen-containing compounds, phenolic compounds, sitosterols, fatty compounds, and rich source of flavonoids [19].…”
Section: Introductionmentioning
confidence: 99%